ASSESSMENT OF REJUVENATION TECHNOLOGY AND IPNM IN AONLA ORCHARD: A WAY TOWARDS TRANSFORMATION & CONSERVATION OF SENILE AND UNPRODUCTIVE ORCHARD - SHRAVAN KUMAR PANDEY; SUNITA PANDEY; ASHISH KUMAR BAJPAI (The Bioscan, 2018)
Present study was carried out to rejuvenate a 15- year old unproductive senile Aonla orchard at the Horticulture farm of Krishi Vigyan Kendra, P.G. College Ghazipur, U.P. during 2010 to 2015 to assess the Rejuvenation technology in location specific condition for creating awareness in farming community of the Ghazipur district through demonstration. Rejuvenation practices including top working with improved cultivar Narendra Aonla 6 and Narendra Aonla-7 along with IPNM were applied on selected trees. Pooled fruit yield data of experiment indicated that the yield in initial year was low in Top worked plants T1 (24.90 kg/tree) and pruned plants T2 (25.50 kg/tree) as compared to farmers practice T3 (Control) yield i.e.27.00 kg /tree. But due to profuse bearing in subsequent production year i.e. 2014 to 20115 paradigm shift in production was observed. The increased yield of T1 and T2 were observed much higher 90.20 per cent and 44.80 per cent respectively over farmers practice(Control:T0). However, economic analysis revealed that B:C ratio were reported higher in T1 (5.8) than the T 2(4.44) and farmers practice T3(3.27). The technology was demonstrated to farmers by organizing field visit time to time to orient the growers